How smartphones can bring about a developmental breakthrough in agriculture - Nirupam Bajpai; Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
Modern smartphones come with high computing power, a variety of sensors and customization abilities that allow creation of a range of practical applications (apps). These features, coupled with the mobility and accessibility in terms of cost that smartphones offer, make them a potential game-changer for smallholder farmers in developing countries, particularly for these farmers' information needs. Smartphones can also make accessing government benefits, land records and crop survey requirements etc. more convenient for farmers. This paper explores how smartphones can be used in different ways, right from production planning to eventual sale of crop. Advanced applications like IoTs, drone use in conjunction with smartphones and design and willingness to pay aspects have also been covered. We believe that given the contemporary trends of robust low-cost devices (e.g., the JioPhone Next etc.) coupled with competitive data tariffs, smartphone use in agriculture will be beneficial for Indian farmers. In fact, the Indian experience can boost similar developments in the developing world, particularly in Africa.
Keywords: 330; Landwirtschaft; Mobiltelefon; Mobile Anwendung; Indien; Entwicklungsländer